PUBLIC FINANCIAL MANAGEMENT AND CORRUPTION IN INDONESIA: A PANEL COINTEGRATION AND CAUSALITY ANALYSIS - Sugeng Triwibowo (Faculty of Economics and Business, Universitas Gadjah Mada, 2020)
Introduction/Main Objectives: This paper aims to examine the relationship between the quality of public financial management and corruption in Indonesia. Background Problems: Despite the impressive progress on the quality of public financial management (PFM) after the financial reforms, Indonesia is still struggling to combat corruption. This raises the question of the effectiveness of the public financial reforms that have been carried out in support of the eradication of corruption. Novelty: This study found empirical evidence of a significant long-run and causal relationship between the quality of public financial management and corruption. Research Methods: This study employs panel cointegration and causality analysis with panel data on the Corruption Perception Index (CPI) and audit opinions for the period from 2006 to 2017. Findings/Results: This study found empirical evidence of the existence of a long-run relationship between the quality of public financial management and corruption and can verify the significant causal relationship between them. In the long run, sound public financial management could significantly encourage clean government. Conclusion: The Government of Indonesia (GoI) should continue its commitment to improve the management of public finances. Meanwhile, the Audit Board of Indonesia (ABI) is expected to strengthen its role to prevent and detect corruption, and to continuously enhance its methods and capacity to improve the execution of its duties and authority.